Water supply, sanitation and water quality improvement : course of lectures in the discipline - Dushkin, Stanislav Sergeyevich (Харківський національний автомобільно-дорожній університет, 2025)
The course of lectures is developed in accordance with the requirements of the educational and professional programme ‘Ecology and Environmental Protection’ of the first (bachelor's) level of higher education in the speciality 101 Ecology for a classroom load of 32 hours (16 lectures). The content of the lectures corresponds to the work programme of the academic discipline OK 34 ‘Water supply, sanitation and water quality improvement’ 2022.
Keywords: water supply; sanitation; water quality improvement; 628.1-3